1367PImpact of sarcopenia in patients with metastatic melanoma treated with immunotherapy. (1st October 2019) - Vitale, M G; Basile, D; Bertoli, E; Giavarra, M; Pelizzari, G; Palmero, L; Zara, D; Targato, G; Pascoletti, G; Cinausero, M; Poletto, E; Iacono, D; et al.
Abstract: Background: High BMI is associated with better survival in metastatic melanoma patients (MM pts), while sarcopenia is linked to poorer outcome in pts with stage III. The aim of this study was to examine the prognostic impact of body-mass index (BMI), baseline sarcopenia, loss of skeletal muscle mass (LSMM) on overall survival (OS) in MM pts who received immunotherapy (IT). Methods: The retrospective series included 42 consecutive MM pts (Jan 2011-Dec 2018) treated with IT in a single referral center. Sarcopenia was defined according to Prado's criteria. Skeletal muscle index (SMI) was calculated as cross-sectional-area of muscle (cm2), using CT-scan, at the L3 level divided by the square of the height (m2). Early LSMM, during IT, was defined as a decrease in SMI > =10% from baseline at first evaluation. BMI was calculated as weight (kg) divided by the square of height (m2) and categorized according to standard WHO definitions. Weight loss was analyzed as continuous variable. Results: At baseline, 27 pts (64, 3%) were male, 26 pts (61.9%) were < 70 years and 31 pts (73.8%) had ECOG PS = 0. Overall, 26 patient (61.9%) had LDH <ULN, 22 pts (52%) had previously received at least one line of systemic therapy. As a first-line IT treatment, 16 pts (38.1%) received a CTLA-4 inhibitor and 26 pts (61.9%) an anti-PD1 agent. Interestingly, 23 pts (54.8%) had a sarcopenic state, and 23 pts (54, 8%) had a BMI > =25. Out of 42 pts, 30 (71.4%) had a CT-scan at first evaluation, and 30% of them had an early LSMM. Median OS was 11.38 months. Both in univariate and multivariate analysis, ECOG PS > =1, and early LSMM > =10% were significantly associated with worse OS. Conversely, pts with weight loss had better OS (Table). Conclusions: Early LSMM > =10% and ECOG PS > =1 may negatively influence the outcome of MM pts treated with IT. Further prospective studies are needed to confirm these data. Legal entity responsible for the study: Maria Grazia Vitale. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.